AmMADS47 of Agropyron mongolicum negatively regulates drought tolerance in rice - Fan, Bobo; Nie, Hushuai; Li, Xiaolei; Ma, Yu; Lv, Ersuo; Wu, Jing; Yan, Xiuxiu; Zhai, Yongqing; Zhao, Yan; Liu, Jie; Du, Xiaohong; Ma, Yanhong (Frontiers in Plant Science, 2025)
MADS-box transcription factors are important regulators of plant abiotic stress response. Despite the exceptional drought tolerance of Agropyron mongolicum, research on the MADS-box transcription factors governing simulate drought stress in this species are limited. In this study, overexpressing AmMADS47 in rice resulted in reduced drought tolerance. Transcriptome sequencing of wild-type (WT) and transgenic rice (OE) at 0 hours of drought and wild-type (WTD) and transgenic rice (OED) at 24 hours of osmotic stress revealed 21,521 differentially expressed genes (DEGs) totally. Further analysis of the top 20 enriched pathways of the DEGs between OE and WT, and between OED and WTD showed that phenylpropanoid biosynthesis and glutathione metabolism were the shared pathways most enriched in DEGs, and photosynthesis-antenna proteins were the shared pathway with the highest enrichment score and significance. Gene regulation in response to osmotic stress was analyzed in the three pathways, showing that, compared to WTD, OED exhibited up-regulation of a few drought-sensitive genes, while most genes positively regulating drought in WTD were down-regulated in OED. Collectively, these results highlight the crucial role of AmMADS47 in modulating the synthesis of key enzymes and the expression patterns of drought-responsive genes in three candidate pathways in rice, ultimately reducing drought resistance in rice.